Multi‐omics analyses reveal the interaction between colonic microbiota and host in Min and Yorkshire pigs - Xiaoyu Huang; Huihui Li; Feng Cheng; Ligang Wang; Guoqing Cao; Lixian Wang; Lijun Shi (Animal Research and One Health)
Abstract Adoption of microbial preparations is becoming more and more prevalent in the pig breeding industry. Digestive tract microbes are recognized as crucial elements affecting physical characteristics of pigs. Until now, it is still challenging to establish connections between colonic microbiome and the host. In this study, weight gain models were created for Min and Yorkshire pigs. The colonic contents and colonic tissues were collected from two pig purebred strains (n = 8/group) with similar weights for multi‐omics analysis. By difference analysis of colonic microbiota, Min pigs observed a significantly higher relative abundance of Bacteroides, Phocaeicola, Roseburia, and Parabacteroides, and Yorkshire pigs had a strongly higher relative abundance of Streptococcus, Vescimonas, Ligilactobacillus, and Lactococcus. Functional annotation showed that the colonic microbiota of Min pigs had extensive dietary polysaccharide and immunomodulatory capacity. Through the correlation analysis of colonic microbiota with metabolomics of colonic content or transcriptomics of colonic tissues, we provided direct and indirect relationships of microorganisms and hosts. By verification, the contents of Occludin, ZO‐1, and pIgR in colonic tissue and sIgA, sIgG, and sIgM in colonic contents of Min pigs were significantly higher than that in Yorkshire pigs. This study revealed characteristics and functions of the colonic microbiota in Min and Yorkshire pigs and analyzed their interactions with the host. Also, we identified immune‐related microorganisms. These results provided a theoretical basis for understanding the influence of colonic microbiota on phenotype shaping in pigs.